Meta-Analysis on the Safety and Cardiorenal Efficacy of SGLT2 Inhibitors in Patients Without T2DM - Li, Lu-Feng; Ding, Liang-Liang; Zhan, Ze-Lin; Qiu, Mei (Frontiers in Cardiovascular Medicine, 2021)
The cardiorenal benefits of sodium-glucose cotransporter 2 (SGLT2) inhibitors in patients with type 2 diabetes mellitus (T2DM) are established, whereas those in patients without T2DM are not established. We sought to assess the cardiorenal efficacy and safety of SGLT2 inhibitors in non-T2DM patients, by performing a meta-analysis based on the subgroup data of non-T2DM patients from relevant secondary analysis articles in which subgroup analyses were done according to the status of diabetes. Compared to placebo, SGLT2 inhibitors significantly reduced heart failure hospitalization (RR 0.70, 95% CI 0.59-0.83) and kidney-specific composite outcome (RR 0.55, 95% CI 0.40-0.75), and increased Kansas City Cardiomyopathy Questionnaire total score by 1.15 (95% CI 1.05-1.25) in patients without T2DM with heart failure (HF) or chronic kidney disease (CKD); whereas gliflozins did not significantly affect cardiovascular death, all-cause mortality, volume depletion, fracture, and amputation in this vulnerable population. There was no one event of major hypoglycemia or diabetic ketoacidosis observed in the non-T2DM subgroup in included trials. These findings will further prompt gliflozins to be used for the prevention of HF and renal failure events and for the improvement of life quality in patients without T2DM with HF or CKD.